KERJASAMA TNI-AD DAN KESATUAN AKSI MAHASISWA INDONESIA (KAMI) DALAM MENJATUHKAN PEMERINTAHAN PRESIDEN SOEKARNO TAHUN 1965-1968 - Nofarof H, Anju Nofarof H; Saiman, Marwoto Saiman; Melay, Ridwan Melay (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrack: University Students’ movement led by the Indonesian Students’ Action Unit (Kesatuan Aksi Mahasiswa Indonesia / KAMI) who has cooperated with the military (Army) in dropping the power of President Soekarno in 1965-1968. Indeed, the student movements should be idealistic and neutral from any party in achieving something. The spirit of the students’ movement is not because of any order or any promised benefits. But, to reveal the truth that is worth fighting for to correct and control the existing government, even overthrow the president. The purpose of this study is to find out why the cooperation of the Army and the Indonesian Students’ Action Unit (KAMI) can be done in striving  to stop the government of President Soekarno in 1965-1968 and how did the struggles done. The method used in this study is historical method and descriptive method. Data obtained through the techniques of literature review, documentation and comparative studies. The research location is in Pekanbaru city in Riau province. The duration of the research started since the proposal seminar until  the thesis seminar. The result of this study is that the cooperation between the army and KAMI caused by the disappointment of political opponents of President Soekarno ever since Guided Democracy  was applied until the implementation of G30S in 1965. The army realized that the power of the supporters of President Soekarno was still strong, and spread throughout the groups. Therefore, the army realized that they needed a partner to cooperate in achieving its goal. Because Indonesian Students’ Action Unit (KAMI) also has its own reasons to fight against President Soekarno. While the task division between the army and the KAMI are : KAMI technically focused on outer side of the government, with demonstrations of anti President Soekarno. While the Army technically focused on inside the government, by weaken the authority and gradually took over the power of President Soekarno, which is called  Crawling Coup (Creeping Coup D'etat). Keywords: Cooperation, Students' Movement, Army, Power, and the Coup.